Identifying the Zika Virus Target Cell in Malignant Glioma. (12th October 2019) - Girdler, Gemma; Gracia, Tannia; Fountain, Daniel; Fajardo Jr, Ted; Finlay, Jack; Hallou, Clément; Pollard, Steve; Sweeney, Trevor; Gergely, Fanni; Rowitch, David; Bulstrode, Harry
Abstract: The Zika Virus epidemic of 2015–2016 was associated with striking failure of forebrain development in infants born to infected mothers, resulting in microcephaly. Studies from numerous labs subsequently confirmed a selective effect of the virus on neural stem cell survival, self-renewal and differentiation. The glioma stem cells which drive glioblastoma and other malignant gliomas depend on neural stem cell transcription programs, so that understanding Zika infection in these cells promises valuable insights into future therapy. We describe here: 1) Study of low passage patient-derived glioblastoma cell lines and normal neural stem cells (CRUK Glioma Cellular Genetics Resource) in adherent culture to address the influence of glioma subtype on infectability 2) Application of genetically modified mCherry reporter Zika Virus strains to address the Zika target cell in glioblastoma. 3) Development of a cerebral organoid model to interrogate the differential effects of the virus on tumour cells and surrounding normal brain. 4) Demonstration of Zika infection on primary patient derived tissue in slice culture format Using these tools we find that Zika targets a common stem cell population across tumour subtypes and neural stem cell controls, and in embryonic and primary tumour explants, and that infection is influenced by activity of cholesterol biosynthesis pathways.